A study on components of interactive projection mapping to enhance youth engagement with Kuda Kepang in Malaysia - Nordin, Syakir Aiman; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Recognizing the declining interest among youth generations and the risk of cultural erosion, the research explored how immersive technologies can preserve intangible heritage. This study analysed the components of interactive projection mapping as a strategy to enhance youth engagement with Kuda Kepang in Malaysia. Kuda Kepang, a traditional Javanese dance with deep spiritual and cultural roots, has seen waning participation in modern times, particularly among youth audiences more attuned to digital forms of entertainment. Employing a qualitative content analysis approach, the study analysed six culturally themed interactive projection mapping works, focusing on four key components which are object, content, interaction, and environment. These elements were critically examined to understand how they influence user engagement, cultural resonance, and experiential impact. The findings revealed that dynamic visuals projected onto three-dimensional objects, combined with real-time audience interaction and carefully curated environments, significantly increase immersion, enjoyment, and emotional connection among youth. By transforming passive cultural presentations into participatory experiences, interactive projection mapping bridged the gap between tradition and contemporary digital expectations. The study concluded that integrating these components offers a promising pathway for sustaining and preserving Kuda Kepang, fostering deeper appreciation and ongoing preservation of Malaysia’s cultural identity among future generations.